International Symposium on Vasoactive Intestinal Peptide, Pituitary Adenylate Cyclase Activating Polypeptide & Related Regulatory Peptides: From Molecular Biology to Clinical Applications: Euroconference, Strasbourg (Bischenberg), 19-23 September 1993 - Gabriel Rosselin [ editor ] (World Scientific, 1994)
Provides information on the class of peptides with high biological activity, which function as hormones or neurotransmitters and have analogous structures. These peptides include the Vasoactive Intestinal Peptide (VIP), and the Pituitary Adenylate Cyclase-Activating Polypeptides (PACAP 38 and 27).